Initialization procedure in solving Optimal Power Flow (OPF) using Artificial Immune System (AIS) optimization technique / Aimi Idzwan Tajudin - Tajudin, Aimi Idzwan (2007)
This project report presents a solution for initializing optimal power flow by using artificial immune system optimization technique. The main consideration in optimal power flow is that the utility strive to minimize its costs and losses while satisfying all of its constraints. By selecting the best of an initial set of control variables from the beginning of the optimization procedure, this method can be work out excellently to achieve the main objective function to minimize instantaneous costs and losses. This paper proposed new approach of selecting initial set of generated and injected reactive power, and also transformer tap changer with less violations of constraint to overwhelm these difficulties. The programmed that has been used in this project is MATLAB, which provides a high level computing language and interactive environment for algorithm development, data visualization, data analysis and numerical analysis. This technique was tested on the IEEE 30 bus reliability test system and results proved that the proposed technique is able to minimize the total costs and total losses of the system.